Determinants of Non-cash Payments in the Eurozone: Culture Matters - Mechthild Schrooten; Armin Varmaz (Vierteljahrshefte zur Wirtschaftsforschung, 2020)
Retail shops incentive contactless transactions during the current COVID-19 pandemic. Customers are asked to pay cashless to prevent contagion. Traditionally, there are large differences in the extent and acceptance of non-cash payments among nations. This paper analyzes empirically the determinants of the payment behavior in the member states of the Eurozone asking how to explain these traditional differences in non-cash payment preferences. Our basic hypothesis is that culture makes the difference across nations matter. The paper adds to the existing literature not only by focusing on the determinants of preferences for non-cash payments from a macroeconomic perspective but also by analyzing cultural factors. The payment data is gathered with the European Central Bank (ECB) and Eurostat. We examine the impact of culture on payment preferences by the means of the Hofstede indicators. Our empirical results show the importance of cultural issues to understand the acceptance of non-cash payments. In particular, the results suggest that a higher degree of uncertainty avoidance goes in line with more non-cash payments. – – Im Zuge der Corona-Pandemie hat der Einzelhandel den Einsatz von non-cash Einzelhandel vorangetrieben. Um eine Covid-Ansteckung zu verhindern, werden Kund*innen gebeten bargeldlos zu zahlen. Tatsächlich es gibt zwischen einzelnen Volkswirtschaften große Unterschiede in der Verwendung von Bargeld und bargeldlosen Zahlungen. Im Beitrag wird empirisch der Frage nachgegangen, welche Faktoren hinter diesen Unterschieden stehen. Die zentrale Hypothese ist, dass Kultur eine große Rolle spielt. Dieses Paper analysiert auf der Grundlage der vorhandenen empirischen Literatur den Einfluss kultureller Faktoren auf den Einsatz von bargeldlosen Zahlungen. Dazu werden nicht nur makroökonomische Daten von der Europäischen Zentralbank und Eurostat, sondern auch die Hofstede Indikatoren herangezogen. Die Ergebnisse zeigen, dass insbesondere die kulturelle Dimension ,,Uncertainty Avoidance" die nationalen Differenzen der gesellschaftlichen Akzeptanz erklären kann. Volkswirtschaften mit einer höheren ,,Uncertainty Avoidance" setzen stärker auf non-cash.
Keywords: E42; G29; G41; 330; Payment systems; cashless payments; culture